Epidural analgesia at trial of labour after caesarean section. A retrospective cohort study over 12 years - Valeria Filippi; Luigi Raio; Sophia Amylidi-Mohr; Rudolf Tschudi; Daniele Bolla (IMR Press, 2021)
Background: Epidural analgesia (EA) in patients at trial of labour after caesarean section (TOLAC) remains a matter of controversy due to fear of masking symptoms suggestive of uterine rupture. The aim of this study was to evaluate if EA during TOLAC increases the risk of maternal and foetal complications. Methods: This study utilized a database containing details of deliveries collected prospectively by a Swiss obstetric study group over a 12-year period. The cohort was dichotomised between women with and without EA during delivery. Contingency tests and Spearman rank correlation were used for statistical analyses. A p < 0.05 was considered significant. Results: Of 4401 women, 1736 (39.4%) were delivered with EA (Group 1) and 2665 (60.6%) without (Group 2). Overall, 56.1% of the women delivered vaginally. Group 1 had a higher vaginal operative delivery birth rate (24.9% vs 9.5%, p < 0.0001) while Group 2 showed a greater rate of emergency caesarean section (49.1% vs 31.50%; p < 0.0001). The overall incidence of uterine rupture was 20/4401 (0.45%) with no difference between groups. Conclusions: EA during TOLAC appears to improve vaginal delivery without increasing maternal and foetal morbidity or uterine ruptur.